Palmyras Reichtum durch weltweiten Handel. Achäologische Untersuchungen im Bereich der hellenistischen Stadt Band 1: Architektur und ihre Ausstattung - Schmidt-Colinet, Andreas (Holzhausen, 2013)
Final publication of an international excavation project in Palmyra/Syria. Publicaation of the architectural features of an hellenistic-roman caravan building: architecture, wall paintings, stucco decorations, restauration reports, material analyses.